Comparison of Methods for Determining Erosion Threshold of Cohesive Sediments Using a Microcosm System - Ha, Hun Jun; Ha, Ho Kyung (Frontiers in Marine Science, 2021)
Erosion of cohesive sediments is a ubiquitous phenomenon in estuarine and intertidal environments. Several methods have been proposed to determine the surface erosion threshold (c0), which are still debatable because of the numerous and uncertain definitions. Based on erosion microcosm experiments, we have compared three different methods using (1) eroded mass (EM), (2) erosion rate (ER), and (3) suspended sediment concentration (SSC), and to suggest a suitable method for revealing the variation of erodibility in intertidal sediments. Erosion experiments using a microcosm system were carried out in the Muuido tidal flat, west coast of Korea. The mean values of c0 for three methods were: 0.20 ± 0.08 Pa (EM); 0.18 ± 0.07 Pa (ER); and (3) 0.17 ± 0.09 Pa (SSC). The SSC method yielded the lowest c0, due to the outflow of suspended sediment from the erosion chamber of the microcosm. This was because SSC gradually decreased with time after depleting the erodible sediment at a given bed shear stress (b). Therefore, the regression between SSC and applied b might skew an x-intercept, resulting in the underestimation (or “not-determined”) of c0. The EM method yielded robust and accurate (within the range of b step at which erosion begins) results. The EM method represents how the erodible depth thickens as b increases and therefore seems better suited than the SSC and ER methods for representing depth-limited erosion of cohesive sediments. Furthermore, this study identified the spatiotemporal variations of c0 by EM method in an intertidal flat. The c0 in mud flat was about two times higher than that in mixed flat. Compared to the end of tidal emersion, the sediment was 10 to 40% more erodible at the beginning stage.